8 - Pentecostal Challenges in Africa and Latin America: A Comparative Focus on Nigeria and Brazil - Olufunke Adeboye, (Afrika Zamani, 2022)
Latin America and Africa are among the continents that have experienced a Pentecostal explosion within the last half century. In fact, each of the case stud- ies for this paper, Nigeria and Brazil, has a very vibrant and visible, though small, Pentecostal component in its population. This paper compares the con- temporary challenges faced by Pentecostals in both countries, and argues that these challenges, to a large extent, are reflective of wider socio-political and economic issues faced by the nations as they grapple with the realities of nation building and related economic issues. A visible impact of this on the Pentecostal movement in both nations is a gradual reduction in the 'other-worldly' focus that had characterized earlier manifestations of Pentecostalism; and a correspond- ing rise in the engagement with temporal or 'this-worldly' concerns. It is in this sense that the shift from classical or traditional Pentecostalism characterized by the holiness doctrine, to what has been dubbed 'neo-Pentecostalism', character- ized, among other things, by the 'prosperity gospel' becomes understandable. In these two countries, there also appears to be an unrelenting negotiation between Pentecostals, who espouse the biblical position of spiritual warfare and deliver- ance on the one hand, and their respective traditional cosmologies, which em- phasize the role of spiritual agents on the other hand. Despite the differences in the socio-political contexts and historical backgrounds of the two countries, it is remarkable that similar processes are discernible in the transformation of the Pentecostal movement and the reaction it has engendered in the larger society.